All drugs are poisons at a higher dose - the case of acute paracetamol poisoning - Palaian, S.; Shankar, P. Ravi; Paudel, R.; Prabhu, M.; Mishra, P. (Journal of Institute of Medicine Nepal, 2007)
Paracetamol is considered to be a safe and effective drug and is available over the counter in many countries including Nepal. Though it is considered safe at its therapeutic dose, it may be toxic at higher dose. It is recognized as a major drug leading to poisoning in the United States of America, United Kingdom and even in Nepal. Several factors such as age of the patients, sex, alcohol intake, disease conditions, concomitant drug intake etc are known to be important factors affecting the severity and outcome of the poisoning. The signs and symptoms are exhibited in a sequential manner and may start with mild nausea and may end with fulminant hepatic failure. Though paracetamol poisoning is associated with many complications and may affect the cardiovascular, respiratory and renal systems, hepatotoxicity is the major complication leading to death. Since paracetamol may be available in combination with other drugs, on many occasions the patient may not present with classical symptoms of paracetamol poisoning. Several laboratory investigations along with the patients’ signs and symptoms help in diagnosis. The management involves symptomatic treatment and a specific antidote mainly N-acetyl cysteine. The estimation of plasma paracetamol concentration is beneficial in diagnosing as well as monitoring the poisoned patient. The pattern and management of paracetamol poisoning varies with the patient populations such as pregnant women, pediatric patients etc. Several strategies including restriction of pack size have been implemented worldwide to prevent the occurrence of paracetamol poisoning. Availability of unbiased drug information is very much essential in management. Journal of Institute of Medicine Vol.28(1) 2006